Experimental investigation on behavior of FRP-strengthened RC beams subjected to combined twisting-bending moments. (1st September 2021) - Ilkhani, M.H.; Naderpour, H.; Kheyroddin, A.
Highlights: Torsional and bending behavior of FRP-strengthened RC beams was investigated. 8 half-scale RC beam specimens divided into two groups were considered. In each group, three specimens were strengthened with the sheets of CFRP. Results for specimens of the two groups were analyzed and compared. Abstract: Even small torsional moments can produce significant stress in beams and alter the behavior of the entire structure. Although many studies on the torsional behavior of reinforced concrete (RC) beams strengthened with fiber-reinforced polymer (FRP) sheets, there are still some uncertainties regarding the behavior of these beams under combined torsional-bending loads. In practice, torsional and bending loads usually occur together, and it is widely believed that the effects of these loads interact and interfere with each other. This study investigated the torsional and bending behavior of FRP-strengthened RC beams under pure torsion and combined torsion-bending. For this investigation, 8 half-scale RC beam specimens divided into two groups of 4 with lengths of 1300 mm and 2300 mm were subjected to pure torsion and combined torsion-bending loads, respectively. In each group, three specimens were strengthened with the sheets of carbon fiber-reinforced polymer (CFRP) with three different configurations, and one beam was left unchanged to serve as the control specimen. Finally, specimens of the two groups were analyzed and compared in terms of cracking torsional strength, ultimate torsional strength, cracking twist angle, and ultimate twist angle.